Disease Characteristics of Inflammatory Bowel Disease (IBD) : Findings from a Tertiary Care Centre in South Asia - Subasinghe, Duminda; Nawarathna, N. M. M.; Samarasekera, Dharmabandhu Nandadeva (Springer, 2011)
Background Inflammatory bowel diseases (IBD) include ulcerative colitis (UC) and Crohn’s disease (CD), which are chronic inflammatory conditions affecting the gastrointestinal tract. There are only few published data on disease characteristics of IBD related to South Asia. Objective To provide the disease characteristics of the IBD patients who presented to a tertiary care hospital in South Asia. Methods Patients with an established diagnosis of IBD were identified after a review of their medical records and demographics, and disease characteristics and indications for surgical treatment were analyzed. Results A total of 184 patients (women = 101, 54.9%; UC = 153, 83.2%) were included. Female preponderance was observed for UC (male/female ratio =1:1.5) and male for CD (male/female = 2:1). Mean age at the time of diagnosis was 36.3 (range 7–71) years. CD was diagnosed at a significantly younger age than UC (27.35 ± 10.22 vs. 38.14 ± 13.05 years, p < 0.0001). CD showed a peak age of onset in the third decade and that for UC was in the fourth decade. The mean duration of IBD was 8.17 (range 1–28) years. Presenting complaint of the majority (73.7%) of UC patients was blood and mucous diarrhea and that for CD (77.4%, 24/31) was left-sided abdominal pain. Only 9.5% (n = 18) had at least one extra-intestinal manifestation. Among UC patients, 51.7% (n = 79) had left-sided colitis and panproctocolitis was found in 18.3% (n = 28). In IBD patients, 14.1% (n = 26) underwent surgery. Only one patient developed malignancy. Conclusions The majority of UC patients had left-sided colitis. CD compared to UC was diagnosed at a younger age. However, compared to data reported for some Western countries, extra-intestinal manifestations and malignancy rates were lower.